JUAL BELI HAK ATAS TANAH BEKAS LAHAN TRANSMIGRASI DI KECAMATAN KARANG BINTANG KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - , Abdul Haris Nasir ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed at knowing the legalities of unnotarized sales and purchases of former transmigration land titles in Karang Bintang Subdistrict, Tanah Bumbu District, Kalimantan Selatan Province and knowing the execution of the registration of land title transfer without any sale and purchase certificates made before PPAT (conveyancers) since the sellersâ domiciles are no longer known. This research employs juridical and empirical approaches since the data used includes both primary data and secondary data. The primary data were collected by interviews with respondents and informants. The respondents are 30 (thirty) former transmigrants and/or third parties who purchased former transmigration land titles in the research location. The informants are the Head of the Land Office of Tanah Bumbu District, the Head of the Manpower and Transmigration Office of Tanah Bumbu District, the Head of Karang Bintang Subdistrict, and 3 (three) village heads in the research location. The secondary data were collected by library research to gather legal material. The research data were organized systematically and analyzed qualitatively. The data were analyzed interpretatively by employing theories or applicable laws. Finally, inductive, conclusions were drawn to answer the problemresearch. The research results show that the sales and purchases of former transmigration land titles in the research location were not made before PPAT. Some of the sales and purchases were made in writing, which were signed by the concerned parties, witnesses, and village heads, but not before PPAT. Others were made verbally by only using receipts as proof of receipt of the payments for the transaction prices. In other words, the sales and purchases were unnotarized. According to the relevant adat law, the unnotarized sales and purchases of land titles are legitimatesince they satisfy two requirements, i.e. expressly and in cash. However, the sales and purchases of land titles, which were not made before PPAT result in the land title transfers from the sellers to the buyers are not able to be registered as required by Article 37 (1) of Government Regulation Number 24 of 1997 concerning Land Registration.